1983
DOI: 10.1111/j.1365-2362.1983.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium malabsorption in the elderly: the effect of treatment with oral 25‐hydroxyvitamin D3

Abstract: Calcium malabsorption is common in the elderly and may contribute to the development of age-related bone loss. To investigate its cause, we have measured radio-calcium absorption, plasma 25-hydroxyvitamin D, 1,25-dihydroxyvitamin D and parathyroid hormone in forty-eight elderly women with a normal plasma creatinine. Calcium malabsorption was associated with low 25-hydroxyvitamin D concentrations and was corrected by increasing these into the normal range by treatment with oral 25-hydroxyvitamin D,. Treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 25 publications
(3 reference statements)
4
45
1
Order By: Relevance
“…Consistent with previous studies suggesting that HyD is more potent than vitamin D 3 in raising 25(OH)D levels, (16)(17)(18)(19)(20)(21) our study shows that 20 mg HyD is significantly more efficient and more rapid in shifting healthy postmenopausal women into a desirable 25(OH)D serum level of at least 30 ng/mL compared to 800 IU (20 mg) vitamin D 3 . Further, our study adds support to the concept that higher 25(OH)D levels may be more desirable for nonskeletal endpoints of vitamin D, including lower extremity function, blood pressure, and immunity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous studies suggesting that HyD is more potent than vitamin D 3 in raising 25(OH)D levels, (16)(17)(18)(19)(20)(21) our study shows that 20 mg HyD is significantly more efficient and more rapid in shifting healthy postmenopausal women into a desirable 25(OH)D serum level of at least 30 ng/mL compared to 800 IU (20 mg) vitamin D 3 . Further, our study adds support to the concept that higher 25(OH)D levels may be more desirable for nonskeletal endpoints of vitamin D, including lower extremity function, blood pressure, and immunity.…”
Section: Discussionsupporting
confidence: 91%
“…(14,15) In earlier studies, oral intake of HyD resulted in a potent increase in serum 25(OH)D levels and parathyroid hormone suppression. (16)(17)(18)(19)(20)(21) Further, some smaller trials reported a benefit on bone density among groups of cardiac and kidney transplant patients, and elderly hip fracture patients (19,22,23) ; although this was not confirmed in a larger trial among 438 seniors. (18) However, the treatment dose of HyD in the larger trial was low with 15 mg per day.…”
Section: Esirable Thresholds For 25(oh)d Have Been Discussedmentioning
confidence: 98%
See 1 more Smart Citation
“…Ca absorption decreases with advancing age (37) , which has been attributed to a number of mechanisms, including the reduction in serum 25(OH)D with age (38) , impaired hydroxylation of 25(OH)D to 1,25(OH) 2 D with declining renal function (39) , resistance to the action of vitamin D metabolites on the bowel mucosa (40) and low circulating oestrogen concentrations in women after the menopause (41) . Increasing serum 25(OH)D concentrations by oral vitamin D supplementation improves Ca absorption in older women, but this is attenuated by renal impairment (42) , suggesting that lower levels of substrate serum 25(OH)D) and impaired hydroxylation of 25(OH)D to 1,25(OH) 2 D both contribute to the decrease in Ca absorption with age. Despite the inverse relationship between dietary Ca intake and Ca absorption, the increase in Ca absorption when dietary Ca is reduced is less marked in older people than younger adults (35) .…”
Section: Calcium Absorptionmentioning
confidence: 99%
“…This may be due to reduced production of 1,25(OH) 2 D, but it may also reflect resistance to the actions of vitamin D metabolites on the bowel, as some studies have shown an attenuated response in Ca absorption to increases in 1,25(OH) 2 D in older women (40) . Although the decline in Ca absorption with advancing age is multifactorial in origin, the improvement in absorption with vitamin D supplementation suggests that vitamin D deficiency is the major cause of malabsorption of Ca in older people (42) . The positive relationship between serum 25(OH)D and fractional absorption extends to 25(OH)D concentrations above 100 nmol/l (42,43) , leading some experts to advocate that these concentrations are necessary for optimal bone health.…”
Section: Calcium Absorptionmentioning
confidence: 99%